The Influence of Brand Image and Product Quality on Customer Loyalty in Petik Madu Lawang Agro tourism - Gultom, Yoel Crhistony; Sa'diyah, Ana Arifatus; Khoirunnisa, Ninin (Journal of Agricultural Socio-Economics (JASE), 2021)
This study aims to analyze the effect of brand image and product quality on customer loyalty in Petik Madu Lawang Agrotourism. This study uses primary data with sampling techniques using non-systematic sampling techniques, namely accidental sampling technique. The study was conducted for 2 months, and it was determined that there were 119 samples. The sample was analyzed using path analysis. The results of the analysis show that the variables of brand image and product quality have a significant effect on customer loyalty positively in Petik Madu Lawang Agrotourism